Translated Article Why Did They Rise Up? The Local Reality of the Farmers’ Movement in 1970s Thailand - Shigetomi , Shinichi; sattayanurak, attachak (CMU Journal of Law and Social Sciences, 2023)
In mid-1970s Thailand, an intense farmers’ movement gathered pace. This study focuses on this village-level movement and investigates why and how farmers took the risk of protesting. It finds that the movement was organized by small groups of villagers or through networks of individuals rather than a wide-ranging mobilization of underprivileged farmers. The villagers’ sense of justice, and not merely their economic grievances, led them to rise up in protest. Taking the case of the northern and central regions, the movement should be regarded as a combination of different organizational structures and strategies rather than a unified national movement.